Inovasi Manajemen Penyiaran dan Peliputan Jurnalisme Modern di Tengah Perkembangan Media Sosial Digital Nasional Terkini - Nia Handayani; Ryan Hidayat; Nila Anggraini; Tio Amanda; Rio Irawan Munthe; Winda Kustiawan (Lembaga Pengembangan Kinerja Dosen, 2026)
This study examines innovation in broadcasting management and modern journalism coverage amid the rapid development of national digital social media in Indonesia. Digital transformation has compelled broadcasting media and journalism institutions to adapt to changes in public information consumption patterns that are increasingly fast, interactive, and platform-based. This study aims to analyze forms of innovation in broadcasting management as well as modern journalism coverage strategies implemented by national media in utilizing social media as channels for news production and distribution. The research employs a qualitative approach through a literature study of national academic journals and conceptual analysis of contemporary digital media practices. The findings indicate that innovations in broadcasting management are reflected in media convergence, the adoption of digital technologies, data-driven newsroom management, and cross-platform collaboration. Meanwhile, modern journalism coverage is characterized by rapid news production, the use of multimedia content, audience engagement, and emerging ethical and accuracy challenges in the digital environment. This study concludes that innovation in both broadcasting management and modern journalism practices is a crucial factor for the sustainability and competitiveness of national media in the era of digital social media.